A Juridical Analysis of the Validity of Electronic Signatures on Agreements - Lubis, Rayhan Qeis Thufeil; Manurung, Abraham Hadonganan; Lubis, Thondi Akbar Parlindungan (PERAHU (PENERANGAN HUKUM) : JURNAL ILMU HUKUM, 2024)
This research aims to determine the validity of electronic signatures and understand their mechanism. Using a qualitative research method and literature study method, the study found that electronic signatures can have the same legal purpose as conventional signatures if they are made in accordance with the requirements in Article 11 paragraphs (1) and (2) of the ITE Law. The position of an electronic signature is considered valid and has legal force if it uses an electronic system that complies with the regulations in force in Indonesia. Electronic signatures are used as valid evidence if the integrity of the information can be guaranteed and accounted for. They are a sign of self-identification written on a document as proof of identity. In the digital era, with the industrial revolution 4.0, electronic signatures are no longer necessary, making business processes easier and transactions faster. The research concludes that electronic signatures can be used as valid evidence in business and transactions if they meet the requirements of the ITE Law.